Benefits of Regulation vs. Competition Where Inequality Is High: The Case of Mobile Telephony in South Africa - Ryan Hawthorne; Lukasz Grzybowski (Center for Economic Studies and ifo Institute (CESifo), 2019)
We test for the distributional effects of regulation and entry in the mobile telecommunications sector in a highly unequal country, South Africa. Using six waves of a consumer survey of over 134,000 individuals between 2009-2014, we estimate a discrete-choice model allowing for individual-specific price-responsiveness and preferences for network operators. Next, we use a demand and supply equilibrium framework to simulate prices and the distribution of welfare without entry and mobile termination rate regulation. We find that regulation benefits consumers significantly more than entry does, and that high-income consumers and city-dwellers benefit more in terms of increased consumer surplus.
Keywords: L13; L40; L50; L96; 330; mobile telecommunications; competition; entry; discrete choice; inequality